2019
DOI: 10.1101/640060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abnormal morphology biases haematocrit distribution in tumour vasculature and contributes to heterogeneity in tissue oxygenation

Abstract: Oxygen heterogeneity in solid tumours is recognised as a limiting factor for therapeutic efficacy. Vessel normalisation strategies, aimed at rescuing abnormal tumour vascular phenotypes and alleviating hypoxia, have the potential to improve tumour responses to treatments such as radiotherapy and chemotherapy. However, understanding how pathological blood vessel networks and oxygen transport are related remains limited. In this paper, we propose a novel source of oxygen heterogeneity in tumour tissue associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 73 publications
4
7
0
Order By: Relevance
“…However, our data suggest that up to 100D of length is required for an initially compacted RBC distribution to expand and reach a steady distribution when the haematocrit is 10%. This finding supports the view that the cross-sectional distribution of RBCs at low in vivo haematocrits may be away from equilibrium not only in diseased vascular networks, as we previously showed in tumours [14], but also under physiological conditions where inter-bifurcation lengths average fewer than 100D. Further research into the network-level dynamics arising from our results is warranted.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, our data suggest that up to 100D of length is required for an initially compacted RBC distribution to expand and reach a steady distribution when the haematocrit is 10%. This finding supports the view that the cross-sectional distribution of RBCs at low in vivo haematocrits may be away from equilibrium not only in diseased vascular networks, as we previously showed in tumours [14], but also under physiological conditions where inter-bifurcation lengths average fewer than 100D. Further research into the network-level dynamics arising from our results is warranted.…”
Section: Discussionsupporting
confidence: 90%
“…First, our results show that the effect of vessel compression on the downstream partitioning of RBCs is only apparent when discharge haematocrit and the distance between the compression and the bifurcation is sufficiently low. Another study by our group showed that two consecutive bifurcations within a short distance can also alter the partitioning of RBCs at the downstream bifurcation [14]. Furthermore, we showed that interbifurcation distances are much reduced in the tumour micro-environment, and Kamoun et al .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our group has recently identified reduced interbifurcation distance and complex branching topology as sources of haematocrit asymmetry in the context of tumour blood flow. Furthermore, we propose a role for the resulting abnormal partitioning in establishing tumour tissue hypoxia(58).…”
mentioning
confidence: 95%